Comparison of in vivo vs. frozen vs. Thiel cadaver specimens in visualisation of anatomical structures of the ankle on proton density Magnetic Resonance Imaging (MRI) through a visual grading analysis (VGA) study. Issue 2 (May 2017) - Zarb, F.; McNulty, J.; Gatt, A.; Formosa, C.; Chockalingam, N.; Evanoff, M.G.; Rainford, L.
Abstract: Purpose: The use of cadavers for medical education purposes and for radiology research methodologies which involve subjective image quality evaluation of anatomical criteria is well documented. The aim of this study was to quantify the impact of cadaver tissue preservation in producing MR images that are representative of living tissue by comparing the visualisation of anatomical structures of the ankle obtained from live and cadaver (fresh frozen and Thiel embalmed) specimens through a visual grading analysis (VGA) study. Methods: A VGA study was conducted on an image data set consisting of 4 coronal proton density weighted (PDw) sequences obtained from ankles of a live patient and those of a cadaveric specimen, of which the right ankle was frozen and the left Thiel embalmed. Results: Comparison of the image quality scores obtained from: the live patient vs. the Thiel specimen indicate a significant difference (p ≤ 0.05) between the scores in favour of the Thiel specimen; between the live patient vs. the frozen specimen indicate a significant difference (p ≤ 0.05) in favour of the frozen specimen and between the frozen vs. the Thiel specimen indicate a significant difference (p ≤ 0.05) in favour of the Thiel specimen. Conclusions: The advantages of the use of cadavers (frozen or Thiel embalmed) has been shown to also apply for use with proton density (PD) MR imaging. The preservation of cadavers especially using Thiel is a suitable alternative for MRI optimisation and protocol development purposes. Highlights: Thiel preservation: a better alternative compared to frozen methods for MR image analysis. VGA demonstrated an efficient research study design for the investigation of embalming methods. Thiel embalmed cadavers: an acceptable alternative from patients for MR imaging optimisation. Additional MR sequences and increased sample sizes are recommended for further investigation.